안산 도심지 계절별 PM1 화학적 성분 특성 - 박종성; 김종법; 신수현; 김필호; 김창혁; 황규철; 이재영; 조석연; 김정호 (환경분석과 독성보건, 2023)
In this study, chemical properties of particulate matter (PM1) present in the urban area of Ansan in 2021 were analyzed using a high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS). Intensive observation was conducted during the measurement periods of spring (22 days), summer (29 days), autumn (60 days), and winter (29 days). High concentrations of PM1 were observed when a wind speed was low (< 0.81 m/s) and a direction of air flow was the east. PM1 concentration was the highest in spring (March), followed by summer (June and August), winter (December), and autumn (September and October). The main components of PM1 were organic, followed by nitrate, ammonium, and sulfate. The ratio of organic oxygen to organic carbon (O/C) was high in summer (0.64) and low in winter (0.51); conversely, the ratio of organic hydrogen to organic carbon (H/C) was higher in winter (1.66) than in summer (1.58). As for the oxidation rates of inorganic components, the nitrogen oxidation rate and sulfur oxidation rate were the highest in spring (NOR, 0.12; SOR, 0.64), which directly affected the rise in PM1 mass concentration in spring. Highly soluble nitrate was the largest component among the inorganic components of PM1, and the PM1 was found to be rich in ammonium in all seasons. PM1mass concentration and chemical composition increased with an increase of relative humidity (RH): the concentration of PM1 in wet conditions (RH > 60%) was found to be more than twice of that in dry conditions (RH < 40%). The largest component of PM1 in Ansan consisted of organic compounds; however, a high proportion of inorganic components, including nitrate, was also recorded.
Keywords: PM1; HR-ToF-AMS; Chemical Components; NOR (nitrogen oxidation rate); SOR (sulfur oxidation rate)